Rebuilding the Vascular Network: In vivo and in vitro Approaches - Meng, Xiangfu; Xing, Yunhui; Li, Jiawen; Deng, Cechuan; Li, Yifei; Ren, Xi; Zhang, Donghui (Frontiers in Cell and Developmental Biology, 2021)
As the material transportation system of the human body, the vascular network carries the transportation of materials and nutrients. Currently, the construction of functional microvascular networks is an urgent requirement for the development of regenerative medicine and in vitro drug screening systems. How to construct organs with functional blood vessels is the focus and challenge of tissue engineering research. Here in this review article, we first introduced the basic characteristics of blood vessels in the body and the mechanism of angiogenesis in vivo, summarized the current methods of constructing tissue blood vessels in vitro and in vivo, and focused on comparing the functions, applications, and advantages of constructing different types of vascular chips to generate blood vessels. Finally, the challenges and opportunities faced by the development of this field were discussed.